O desenvolvimento do pensamento teórico no ensino da termodinâmica em situações desencadeadoras de aprendizagem - Santos, Rogério de Souza (2018)
The present research had as objective to analyze the development of the theoretical thought in Thermodynamics from the process of signification of students of High School generated in situations triggering of learning. In order to achieve this general objective, the research had the following specific objectives: to analyze how the elements of mediation produced by human culture triggers the process of signification that provoke the development of student thinking; to analyze the potential of the situations triggering learning that make up the didactic unit in the creation of the zone of impending development, mobilizing the subjects to carry out the study activities. The Historical-Cultural Theory of Activity and the Theory of Developmental Teaching formed the structuring foundation of research, guiding the intentionality of the teacher in his teaching activity, including the elaboration of the Didactic Unit. The development of the educational product was carried out with students of the second year of High School integrated technical courses and, in particular, with a third year class of the High School of the integrated technical course of Mechanical Maintenance, since the Thermodynamics was part of the curricular component for this step. In developing the tasks of this Didactic Unit, the students were mediated in their learning activities by the teacher, who in their teaching activity guided them in the social construction of the concepts of thermodynamics through theoretical thinking. The guiding question of the present research was: what conceptual elaborations are produced by the students when trying to develop the theoretical thinking about the laws of Thermodynamics through situations triggering learning? For the production of the research data, audio recorders, field notes of the teacher and the tasks of the Educational Product were used, which provided spaces for the students’ textual production. Thus, the corpus of research was constituted by the textual productions of the students in the conceptual elaborations of the laws of Thermodynamics, by the audio transcriptions that captured the process of production and negotiation of meanings in the Didactic Unit and by the field notes of the researcher. The planning of the sequence of Thermodynamics classes, the lesson scripts and a synthesis of the theory that guided us in our intentionality of teaching make up the Didactic Unit or Educational Product. This didactic unit was developed in the middle of the first quarter of the 2017 school year at the Federal Institute of Minas Gerais, after working the concepts of hydrostatics, with which we worked with the same theoretical perspective of learning. With the construction of the corpus of analysis, the categories of analysis were constructed through discursive textual analysis. The priori category was the laws of thermodynamics, to analyze the structure of didactic unit and the conceptual nexus. The posteriori categories or emergent were to the mediation and the false passivity of the students, to analyze the classes in perspective of the historical-cultural theory of the activity of the Educational Product. Initially the students flowed in empirical thinking, grouping the empirical data, going through a process of meaning of the concepts of thermodynamics without being able to define them. As the tasks unfolded, the students were able to understand the concepts through a collective construction, socializing the impressions giving coherent interpretations to the empirical data and synthesizing them into concepts. In the final part of the development of the tasks students operated by concepts, characteristic of the development of theoretical thinking. Mediation was characterized by a complex element, since it is an operation done by instruments such as cell phones and books, signs, besides having the teacher as a bridge between where they are and the content to be reached. We also analyze that all students are active, because according to Leontiev (1978) the activity is inherent to the human being, except that he is sleeping or vegetating, the intellectual functions are always active, being able to be in a different activity that not necessarily the activity of studies.re they are and the content to be reached. With this, in the planning of the classes, the teacher created teaching-triggering situations that in practice produced an imminent zone of development, drawing the attention and interest of students in study activities.